1990
DOI: 10.1038/345041a0
|View full text |Cite
|
Sign up to set email alerts
|

A binding site for the T-cell co-receptor CD8 on the α3 domain of HLA-A2

Abstract: Adhesion measurements between CD8 and 48 point mutants of HLA-A2.1 show that the CD8 alpha-chain binds to the alpha 3 domain of HLA-A2.1. Three clusters of alpha 3 residues contribute to the binding, with an exposed, negatively charged loop (residues 223-229) playing a dominant role. CD8 binding correlates with cytotoxic T-cell recognition and sensitivity to inhibition by anti-CD8 antibodies. Impaired alloreactive T-cell recognition of an HLA-A2.1 mutant with reduced affinity for CD8 is not restored by functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
266
0
4

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(277 citation statements)
references
References 48 publications
7
266
0
4
Order By: Relevance
“…2c). This finding is similar to that reported by Salter et al, 5 , who noted that T-cell recognition of a3 mutant class I molecules is particularly sensitive to anti-CD8 blocking. Secondary C3H anti-L Q3 CTL recognize both L d and L Q3 and these responses are resistant to blocking by anti-CD8 (Fig.…”
supporting
confidence: 92%
“…2c). This finding is similar to that reported by Salter et al, 5 , who noted that T-cell recognition of a3 mutant class I molecules is particularly sensitive to anti-CD8 blocking. Secondary C3H anti-L Q3 CTL recognize both L d and L Q3 and these responses are resistant to blocking by anti-CD8 (Fig.…”
supporting
confidence: 92%
“…Both the CD8 ␣-and ␤-chains are composed of a single extracellular Ig superfamily (IgSF) 3 variable (V) domain, a membrane-proximal hinge (H) region, a transmembrane domain (TM), and a cytoplasmic tail (CY). Biochemical and structural studies have shown that the Ig V domain of CD8␣, in conjunction with that of CD8␤, interacts with MHC class I molecules, thereby allowing the CD8 molecule to function as a coreceptor of the T cell Ag receptor (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…In this consideration, the accessibility for human CD8 coreceptors and the SLA molecules on donor endothelium of blood vessel cannot be neglected [20]. The key residues on SLA class I molecule is located in a3 domain, a segment with no polymorphism [21]. To compare the critical sequences of the a3 domain in human (HLA-A * 0201) and in the Chinese pig stains, six amino acid residues from 223 to 228 were checked.…”
Section: The Human Kir-recognized Ligand Sequences In the Class I Molmentioning
confidence: 99%